Pengaruh Tingkat Keuntungan, Literasi Keuangan Syariah dan Religiusitas Terhadap Minat Investasi Emas Syariah di Kalangan Generasi Z Kabupaten Jepara - Richa Armelia Rokhmah; Edi Susilo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The objective of this study is to examine the effect of return rate, Islamic financial literacy, and religiosity on the intention to invest in Sharia-compliant gold among Generation Z in Jepara Regency. The novelty of this study lies in integrating Islamic financial literacy and religiosity within the context of Sharia-compliant gold investment among Generation Z in Jepara Regency, which has rarely been examined simultaneously. In addition, this study employs a survey-based quantitative approach focusing on investment intention through digital platforms, thereby offering a new perspective on the investment behavior of a technologically literate and religiously oriented young generation. This study uses a quantitative approach with a survey method to analyze the effect of return rate and knowledge on investment intention. The data used are primary data obtained from Generation Z respondents through questionnaire distribution. The population of this study consists of Generation Z in Jepara Regency who are actively engaged in investment activities. The sampling technique employed is purposive sampling, with a total sample of 95 Generation Z respondents in Jepara Regency. Data were collected using a Likert-scale questionnaire. The analytical technique applied is multiple linear regression analysis using SPSS version 26. The results indicate that the return rate has a positive and significant effect on the intention to invest in Sharia-compliant gold. Islamic financial literacy has a positive and significant effect on the intention to invest in Sharia-compliant gold. Religiosity also has a positive and significant effect on the intention to invest in Sharia-compliant gold.